A corrosion-resistant cable for charging piles
By using a combination of modified glass fiber powder and polytetrafluoroethylene powder in the outer sheath layer of the charging pile cable, the problem of insufficient corrosion resistance and wear resistance of the existing cable outer sheath layer is solved, and higher corrosion resistance and wear resistance are achieved.
Patent Information
- Application Number
- CN202410682007.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-29
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-05-29
AI Technical Summary
The external sheath layer of existing charging pile cables is insufficient in corrosion resistance and wear resistance, making it difficult to meet the high requirements of modern charging technology for cables.
Rubber and polytetrafluoroethylene powder are used as the base material for the outer sheath layer of the cable, and glass fiber powder modified by γ-aminopropyltrimethoxysilane and 2-(4-amino-2-nitroaniline)ethanol are improved to improve the corrosion resistance and wear resistance of the outer sheath layer.
The corrosion resistance and wear resistance of the outer sheath layer of the cable are significantly improved, the wear amount and the loss of tensile strength under acid etching conditions are reduced, and the overall performance of the cable is improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cables, and in particular to a corrosion-resistant cable for a charging pile. Background Art
[0002] With the popularization of electric vehicles and the development of technology, as well as the promotion of the government's electric vehicle charging policy, the electric vehicle charging pile industry has made great progress. Among them, the charging pile cable, as a carrier for transmitting electric energy between electric vehicles and charging piles, has also received more and more attention. Modern charging technology has higher and higher requirements for the charging process, requiring information transmission between electric vehicles and charging piles, and being able to make appropriate control of the charging action. Therefore, in addition to ensuring excellent insulation performance, the electric vehicle charging pile cable should also have high corrosion resistance and wear resistance to reduce possible injuries and economic losses in accidents. Therefore, the preparation of a charging pile cable with high corrosion resistance and wear resistance is a problem that needs to be solved. Summary of the invention
[0003] The present invention provides a corrosion-resistant cable for a charging pile, which solves the problem of poor corrosion resistance and wear resistance of the outer sheath layer of the cable in the related art.
[0004] The technical solution of the present invention is as follows:
[0005] The present invention provides a corrosion-resistant cable for a charging pile, which comprises, from inside to outside, a cable core, an inner protective sheath, a shielding layer, a heat insulating layer, and an outer protective sheath. The cable core is composed of a plurality of wire cores, and the wire core is composed of a conductor and an outer insulating layer of the conductor. The outer protective sheath comprises the following raw materials in parts by weight: 80-90 parts of rubber, 10-15 parts of polytetrafluoroethylene powder, 1-3 parts of vulcanizer, 10-15 parts of plasticizer, 2-4 parts of lubricant, 0.8-1 parts of accelerator, 1-3 parts of antioxidant, and 30-40 parts of modified filler.
[0006] The modified filler is obtained by modifying glass fiber powder with a modifier, and the modifier includes γ-aminopropyltrimethoxysilane and / or 2-(4-amino-2-nitroanilino)ethanol.
[0007] As a further technical solution, the modifier consists of γ-aminopropyltrimethoxysilane and 2-(4-amino-2-nitroanilino)ethanol.
[0008] As a further technical solution, the mass ratio of the γ-aminopropyltrimethoxysilane to 2-(4-amino-2-nitroanilino)ethanol is 1-7:1.
[0009] In the present invention, the glass fiber powder is modified by γ-aminopropyltrimethoxysilane and 2-(4-amino-2-nitroanilino)ethanol, so that the corrosion resistance and wear resistance of the cable outer sheath layer are improved, and the corrosion resistance and wear resistance of the cable outer sheath layer are further improved by limiting the mass ratio of γ-aminopropyltrimethoxysilane and 2-(4-amino-2-nitroanilino)ethanol to 1-7:1.
[0010] As a further technical solution, the mass ratio of the γ-aminopropyltrimethoxysilane to 2-(4-amino-2-nitroanilino)ethanol is 3:1.
[0011] As a further technical solution, the amount of the modifier added is 2% to 4% of the mass of the glass fiber powder.
[0012] In the present invention, by limiting the addition amount of the modifier to 2% to 4% of the mass of the glass fiber powder, the corrosion resistance and wear resistance of the outer sheath layer of the cable are improved.
[0013] As a further technical solution, the added amount of the modifier is 3% of the mass of the glass fiber powder.
[0014] As a further technical solution, the modified filler is glass fiber powder which is first modified with γ-aminopropyltrimethoxysilane and then modified with 2-(4-amino-2-nitroanilino)ethanol for a second time to obtain the modified filler.
[0015] As a further technical solution, the preparation method of the modified filler comprises the following steps:
[0016] S1, adding glass fiber powder to N-methylpyrrolidone, and then adding γ-aminopropyltrimethoxysilane to perform the first modification, and obtaining modified glass fiber powder by centrifugation, washing and drying;
[0017] S2. Ultrasonic dispersion of the modified glass fiber powder in toluene, addition of 2-(4-amino-2-nitroanilino)ethanol, a second modification, and centrifugation, washing, and drying to obtain a modified filler.
[0018] As a further technical solution, the temperature of the first modification is 30-40° C., and the time of the first modification is 3-5 hours.
[0019] As a further technical solution, the temperature of the second modification is 45° C., and the time of the second modification is 4 hours.
[0020] As a further technical solution, the rubber is butyl rubber and / or chloroprene rubber.
[0021] As a further technical solution, the particle size of the glass fiber powder is 2000 mesh.
[0022] As a further technical solution, the vulcanizing agent includes one or more of sulfur, diisopropyl peroxide, and 1,3-bis(tert-butylperoxyisopropyl)benzene.
[0023] As a further technical solution, the plasticizer includes one or more of plasticizer DOTP, plasticizer TOTM, and plasticizer DPHP.
[0024] As a further technical solution, the lubricant includes one or more of stearic acid, calcium stearate, and polyethylene wax.
[0025] As a further technical solution, the accelerator includes one or more of accelerator M, accelerator TMTD, and accelerator TTTE.
[0026] As a further technical solution, the antioxidant includes one or more of antioxidant RD, antioxidant 4020, and antioxidant MB.
[0027] The present invention also proposes a method for preparing a corrosion-resistant cable for a charging pile, comprising the following steps:
[0028] S1, extrude the insulating layer material onto the outside of the conductor to form a wire core;
[0029] S2, arranging multiple wire cores in a ring array to form a cable core, and extruding an inner protective sheath material on the outer side of the cable core to form an inner protective sheath layer;
[0030] S3, winding the shielding layer material around the outer side of the inner protective sleeve layer to obtain a shielding layer;
[0031] S4, extruding a heat insulation layer material on the outer side of the shielding layer to obtain a heat insulation layer, thereby obtaining a semi-finished cable;
[0032] S5. Rubber, polytetrafluoroethylene powder, plasticizer, lubricant, accelerator, antioxidant and modified filler are mixed and then vulcanized with a vulcanizing agent to obtain a rubber compound. The rubber compound is extruded and wrapped on the outside of the semi-finished cable through an extruder to obtain a corrosion-resistant cable.
[0033] As a further technical solution, the mixing time is 10 to 20 minutes.
[0034] As a further technical solution, the shielding layer material is an aluminum-plastic composite tape.
[0035] As a further technical solution, the thermal insulation layer material is silicone rubber.
[0036] The working principle and beneficial effects of the present invention are:
[0037] In the present invention, rubber and polytetrafluoroethylene powder are used as the base material of the cable outer sheath layer, so as to improve the corrosion resistance of the outer sheath layer. In addition, glass fiber powder modified with γ-aminopropyltrimethoxysilane and 2-(4-amino-2-nitroanilino)ethanol is added to further improve the corrosion resistance and wear resistance of the outer sheath layer. DETAILED DESCRIPTION
[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] In the following embodiments and comparative examples:
[0040] Butyl rubber, model 1675N, purchased from Guangzhou Liben Rubber Raw Materials Trading Co., Ltd.;
[0041] Neoprene, model S-40V-1, purchased from Guangdong Dingxin Polymer Technology Co., Ltd.;
[0042] Glass fiber powder, particle size 2000 mesh, was purchased from Donghai County Fucai Mineral Products Co., Ltd.
[0043] Example 1
[0044] A method for preparing a corrosion-resistant cable for a charging pile comprises the following steps:
[0045] S1, extrude the insulating layer material onto the outside of the conductor to form a wire core;
[0046] S2, arranging multiple wire cores in a ring array to form a cable core, and extruding an inner protective sheath material on the outer side of the cable core to form an inner protective sheath layer;
[0047] S3, wrapping an aluminum-plastic composite tape around the outer side of the inner protective sleeve layer to obtain a shielding layer;
[0048] S4, extruding silicone rubber on the outer side of the shielding layer to obtain a heat insulation layer, thereby obtaining a semi-finished cable;
[0049] S5. Mix 80 parts of butyl rubber, 10 parts of polytetrafluoroethylene powder, 10 parts of plasticizer DOTP, 2 parts of stearic acid, 0.8 parts of accelerator M, 1 part of antioxidant RD and 30 parts of modified filler for 10 minutes, then add 1 part of sulfur for vulcanization to obtain a rubber compound, and extrude the rubber compound onto the outside of the cable semi-finished product through an extruder to obtain a corrosion-resistant cable.
[0050] Preparation method of modified filler: add 40g glass fiber powder (2000 mesh) into 400mL N-methylpyrrolidone, then add 0.4g γ-aminopropyltrimethoxysilane, stir at 30°C for 5h, and obtain modified filler by centrifugation, washing and drying.
[0051] Example 2
[0052] A method for preparing a corrosion-resistant cable for a charging pile comprises the following steps:
[0053] S1, extrude the insulating layer material onto the outside of the conductor to form a wire core;
[0054] S2, arranging multiple wire cores in a ring array to form a cable core, and extruding an inner protective sheath material on the outer side of the cable core to form an inner protective sheath layer;
[0055] S3, wrapping an aluminum-plastic composite tape around the outer side of the inner protective sleeve layer to obtain a shielding layer;
[0056] S4, extruding silicone rubber on the outer side of the shielding layer to obtain a heat insulation layer, thereby obtaining a semi-finished cable;
[0057] S5. Mix 85 parts of chloroprene rubber, 12 parts of polytetrafluoroethylene powder, 12 parts of plasticizer TOTM, 3 parts of calcium stearate, 0.9 parts of accelerator TMTD, 2 parts of antioxidant 4020 and 35 parts of modified filler for 12 minutes, then add 2 parts of diisopropylbenzene peroxide for vulcanization to obtain a rubber compound, and extrude the rubber compound onto the outside of the cable semi-finished product through an extruder to obtain a corrosion-resistant cable.
[0058] Preparation method of modified filler: add 40g glass fiber powder (2000 mesh) into 400mL N-methylpyrrolidone, then add 1.2g γ-aminopropyltrimethoxysilane, stir at 35°C for 4h, and obtain modified filler by centrifugation, washing and drying.
[0059] Example 3
[0060] A method for preparing a corrosion-resistant cable for a charging pile comprises the following steps:
[0061] S1, extrude the insulating layer material onto the outside of the conductor to form a wire core;
[0062] S2, arranging multiple wire cores in a ring array to form a cable core, and extruding an inner protective sheath material on the outer side of the cable core to form an inner protective sheath layer;
[0063] S3, wrapping an aluminum-plastic composite tape around the outer side of the inner protective sleeve layer to obtain a shielding layer;
[0064] S4, extruding silicone rubber on the outer side of the shielding layer to obtain a heat insulation layer, thereby obtaining a semi-finished cable;
[0065] S5. Mix 45 parts of butyl rubber, 45 parts of chloroprene rubber, 15 parts of polytetrafluoroethylene powder, 15 parts of plasticizer DPHP, 4 parts of polyethylene wax, 1 part of accelerator TTTE, 3 parts of antioxidant MB and 40 parts of modified filler for 15 minutes, then add 3 parts of 1,3-bis(tert-butylperoxyisopropyl)benzene for vulcanization to obtain a rubber compound, and extrude the rubber compound onto the outside of the cable semi-finished product through an extruder to obtain a corrosion-resistant cable.
[0066] Preparation method of modified filler: add 40g glass fiber powder (2000 mesh) into 400mL N-methylpyrrolidone, then add 2g γ-aminopropyltrimethoxysilane, stir at 40°C for 3h, and obtain modified filler by centrifugation, washing and drying.
[0067] Example 4
[0068] The difference between this embodiment and embodiment 1 is that γ-aminopropyltrimethoxysilane is replaced by an equal amount of 2-(4-amino-2-nitroanilino)ethanol.
[0069] Example 5
[0070] Compared with Example 1, this embodiment is different from Example 1 in that the preparation method of the modified filler is as follows: S1, 40 g of glass fiber powder (2000 mesh) is added to 400 mL of N-methylpyrrolidone, and then 0.02 g of γ-aminopropyltrimethoxysilane is added, and the mixture is stirred at 30° C. for 5 h, and the modified glass fiber powder is obtained by centrifugation, washing, and drying;
[0071] S2. Add the modified glass fiber powder into 300 mL of toluene, add 0.38 g of 2-(4-amino-2-nitroanilino)ethanol, stir at 45° C. for 4 h, and obtain a modified filler by centrifugation, washing, and drying.
[0072] Example 6
[0073] The only difference between this embodiment and embodiment 5 is that the added amount of γ-aminopropyltrimethoxysilane is 0.38 g, and the added amount of 2-(4-amino-2-nitroanilino)ethanol is 0.02 g.
[0074] Example 7
[0075] The only difference between this embodiment and embodiment 5 is that the added amount of γ-aminopropyltrimethoxysilane is 0.2 g, and the added amount of 2-(4-amino-2-nitroanilino)ethanol is 0.2 g.
[0076] Example 8
[0077] The difference between this embodiment and embodiment 5 is that the added amount of γ-aminopropyltrimethoxysilane is 0.3 g, and the added amount of 2-(4-amino-2-nitroanilino)ethanol is 0.1 g.
[0078] Example 9
[0079] The only difference between this embodiment and embodiment 5 is that the added amount of γ-aminopropyltrimethoxysilane is 0.35 g, and the added amount of 2-(4-amino-2-nitroanilino)ethanol is 0.05 g.
[0080] Example 10
[0081] The only difference between this embodiment and embodiment 8 is that the added amount of γ-aminopropyltrimethoxysilane is 1.5 g, and the added amount of 2-(4-amino-2-nitroanilino)ethanol is 0.5 g.
[0082] Embodiment 11
[0083] The only difference between this embodiment and embodiment 8 is that the added amount of γ-aminopropyltrimethoxysilane is 0.6 g, and the added amount of 2-(4-amino-2-nitroanilino)ethanol is 0.2 g.
[0084] Example 12
[0085] The only difference between this embodiment and embodiment 8 is that the added amount of γ-aminopropyltrimethoxysilane is 0.9 g, and the added amount of 2-(4-amino-2-nitroanilino)ethanol is 0.3 g.
[0086] Example 13
[0087] The only difference between this embodiment and embodiment 8 is that the added amount of γ-aminopropyltrimethoxysilane is 1.2 g, and the added amount of 2-(4-amino-2-nitroanilino)ethanol is 0.4 g.
[0088] Comparative Example 1
[0089] A method for preparing a corrosion-resistant cable for a charging pile comprises the following steps:
[0090] S1-S4, same as in Example 1;
[0091] S5. Mix 80 parts of butyl rubber, 10 parts of polytetrafluoroethylene powder, 10 parts of plasticizer DOTP, 2 parts of stearic acid, 0.8 parts of accelerator M, 1 part of antioxidant RD, and 30 parts of glass fiber powder (2000 mesh) for 10 minutes, then add 1 part of sulfur for vulcanization to obtain a rubber compound, and extrude the rubber compound onto the outside of the cable semi-finished product through an extruder to obtain a corrosion-resistant cable.
[0092] The wear amount of the outer sheath layer of the cable prepared in Examples 1 to 13 and Comparative Example 1 was tested according to the test method in GB / T 9867-2008 "Determination of wear resistance of vulcanized rubber or thermoplastic rubber (rotating roller abrasion machine method)"; the corrosion resistance was measured by the following method: after the outer sheath layer was immersed in a 20wt% sulfuric acid solution for 30 days, the tensile strength before and after immersion was tested according to the test method in GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber", and the tensile strength retention rate was calculated, and the calculation formula was: tensile strength retention rate (%) = tensile strength after immersion / tensile strength before immersion × 100. The specific test results are shown in Table 1.
[0093] Performance test results of the cable outer sheath layer prepared in Examples 1 to 13 and Comparative Example 1
[0094]
[0095] Compared with Example 1, the glass fiber powder was not modified in Comparative Example 1. As a result, the wear amount of the cable outer sheath layer prepared in Comparative Example 1 was higher than that in Example 1, and the retention rate of tensile strength under acid etching conditions was lower than that in Example 1, indicating that by adding glass fiber powder modified with γ-aminopropyltrimethoxysilane, the wear amount of the cable outer sheath layer can be reduced and the corrosion resistance can be improved.
[0096] Compared with Example 1, Example 4 is modified by 2-(4-amino-2-nitroanilino)ethanol, and Example 5 is modified by γ-aminopropyltrimethoxysilane and 2-(4-amino-2-nitroanilino)ethanol. As a result, the wear amount of the cable outer sheath layer prepared in Example 5 is lower than that in Examples 1 and 4, and the tensile strength retention rate under acid etching conditions is higher than that in Examples 1 and 4, indicating that by modifying the glass fiber powder with γ-aminopropyltrimethoxysilane and 2-(4-amino-2-nitroanilino)ethanol, the wear amount of the cable outer sheath layer can be further reduced and the corrosion resistance can be improved.
[0097] Compared with Example 5, Examples 6 to 9 change the mass ratio of γ-aminopropyltrimethoxysilane and 2-(4-amino-2-nitroanilino)ethanol. As a result, the wear amount of the cable outer sheath layer obtained in Examples 7 to 9 is lower than that in Examples 5 and 6, and the tensile strength retention rate under acid etching conditions is higher than that in Examples 5 and 6, indicating that when the mass ratio of γ-aminopropyltrimethoxysilane and 2-(4-amino-2-nitroanilino)ethanol is 1 to 7:1, the wear amount of the cable outer sheath layer can be further reduced and the corrosion resistance can be improved. Comparing Examples 7 to 9, it is found that the wear amount of the cable outer sheath layer obtained in Example 8 is lower than that in Examples 7 and 9, and the tensile strength retention rate under acid etching conditions is higher than that in Examples 7 and 9, indicating that when the mass ratio of γ-aminopropyltrimethoxysilane and 2-(4-amino-2-nitroanilino)ethanol is 3:1, the wear amount of the cable outer sheath layer obtained is the lowest and the corrosion resistance is the highest.
[0098] Compared with Example 8, Examples 10 to 13 changed the amount of modifier added. As a result, the outer sheath layer of the cable obtained in Examples 11 to 13 had a lower wear amount than Examples 8 and 10, and the tensile strength retention rate under acid etching conditions was higher than that of Examples 8 and 10, indicating that when the amount of modifier added was 2% to 4% of the mass of the glass fiber powder, the wear amount of the outer sheath layer of the cable could be further reduced and the corrosion resistance could be improved. Comparing Examples 11 to 13, it was found that the outer sheath layer of the cable obtained in Example 12 had a lower wear amount than Examples 11 and 13, and the tensile strength retention rate under acid etching conditions was higher than that of Examples 11 and 13, indicating that when the amount of modifier added was 3% of the mass of the glass fiber powder, the outer sheath layer of the cable obtained had the lowest wear amount and the highest corrosion resistance.
[0099] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A corrosion-resistant cable for a charging pile, characterized in that: From inside to outside, the cable core, the inner protective sheath, the shielding layer, the heat insulation layer, and the outer protective sheath are arranged in order. The cable core is composed of multiple wire cores, and the wire core is composed of a conductor and an outer insulating layer of the conductor. The outer protective sheath includes the following raw materials in parts by weight: 80-90 parts of rubber, 10-15 parts of polytetrafluoroethylene powder, 1-3 parts of vulcanizer, 10-15 parts of plasticizer, 2-4 parts of lubricant, 0.8-1 parts of accelerator, 1-3 parts of antioxidant, and 30-40 parts of modified filler; The modified filler is obtained by modifying glass fiber powder with a modifier, wherein the modifier is composed of γ-aminopropyltrimethoxysilane and 2-(4-amino-2-nitroanilino)ethanol; The preparation method of the modified filler comprises the following steps: S1, adding glass fiber powder to N-methylpyrrolidone, and then adding γ-aminopropyltrimethoxysilane to perform the first modification, and obtaining modified glass fiber powder by centrifugation, washing and drying; S2. Ultrasonic dispersion of the modified glass fiber powder in toluene, addition of 2-(4-amino-2-nitroanilino)ethanol, a second modification, and centrifugation, washing, and drying to obtain a modified filler.
2. A corrosion-resistant cable for a charging pile according to claim 1, characterized in that: The mass ratio of the γ-aminopropyltrimethoxysilane to 2-(4-amino-2-nitroanilino)ethanol is 1-7:
1.
3. A corrosion-resistant cable for a charging pile according to claim 1, characterized in that: The amount of the modifier added is 2% to 4% of the mass of the glass fiber powder.
4. A corrosion-resistant cable for a charging pile according to claim 1, characterized in that: The rubber is butyl rubber and / or chloroprene rubber.
5. The corrosion-resistant cable for a charging pile according to claim 1, characterized in that: The vulcanizing agent includes one or more of sulfur, diisopropylbenzene peroxide, and 1,3-bis(tert-butylperoxyisopropyl)benzene.
6. The corrosion-resistant cable for a charging pile according to claim 1, characterized in that: The plasticizer includes one or more of plasticizer DOTP, plasticizer TOTM, and plasticizer DPHP.
7. The corrosion-resistant cable for a charging pile according to claim 1, characterized in that: The lubricant includes one or more of stearic acid, calcium stearate, and polyethylene wax.
8. The corrosion-resistant cable for a charging pile according to claim 1, characterized in that: The accelerator includes one or more of accelerator M, accelerator TMTD, and accelerator TTTE.
9. The corrosion-resistant cable for a charging pile according to claim 1, characterized in that: The antioxidant includes one or more of antioxidant RD, antioxidant 4020, and antioxidant MB.
Citation Information
Patent Citations
Chloroprene rubber cable sheathing compound and preparation method thereof
CN103539992A
High-insulativity polyamide resin inflaming retarding and insulating material
CN108467582A